Adiponectin Mediates Running-Restored Hippocampal Neurogenesis in Streptozotocin-Induced Type 1 Diabetes in Mice - Yau, Suk-Yu; Lee, Thomas Ho-Yin; Li, Ang; Xu, Aimin; So, Kwok-Fai (Frontiers in Neuroscience, 2018)
Streptozotocin (STZ)-induced diabetes impairs learning and memory performance and reduces adult hippocampal neurogenesis. Physical exercise brings beneficial effects. We have previously shown that adiponectin, an adipocyte-secreted hormone critically involved in the pathology of diabetes, is a key mediator for exercise-enhanced adult hippocampal neurogenesis. Here, we tested whether adiponectin is required for exercise to restore adult hippocampal neurogenesis in an animal model of diabetes. The findings showed that a single injection of 195 mg/kg STZ-induced diabetes significantly increased serum levels of corticosterone and reduced hippocampal adiponectin levels in adult mice. STZ injection also significantly reduced the number of Ki67 and doublecortin (DCX) positive cells and the ratio of co-labeling of DCX and bromodeoxyuridine (BrdU) in the hippocampal dentate region, indicating a decrease in adult hippocampal neurogenesis. Two-week voluntary wheel running significantly restored hippocampal neurogenesis in the diabetic wild-type mice, but not adiponectin knockout mice, indicating that adiponectin is critical for physical exercise to restore hippocampal adult neurogenesis in mice with diabetes. The results suggest that increasing adiponectin levels could be a therapeutic approach to restore hippocampal neurogenesis impairment in individuals with diabetes.